2015
DOI: 10.1214/14-aap1075
|View full text |Cite
|
Sign up to set email alerts
|

On the topology of random complexes built over stationary point processes

Abstract: There has been considerable recent interest, primarily motivated by problems in applied algebraic topology, in the homology of random simplicial complexes. We consider the scenario in which the vertices of the simplices are the points of a random point process in R d , and the edges and faces are determined according to some deterministic rule, typically leading toČech and Vietoris-Rips complexes. In particular, we obtain results about homology, as measured via the growth of Betti numbers, when the vertices ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 41 publications
1
73
0
Order By: Relevance
“…Theorem 1.12 shows these limits hold for general stationary input. The paper [74] gives a weaker version of Theorem 1.12 for specific ξ and for f = 1[x ∈ W 1 ]. In full generality, the convergence rate (1.23) is new.…”
Section: Remarksmentioning
confidence: 99%
“…Theorem 1.12 shows these limits hold for general stationary input. The paper [74] gives a weaker version of Theorem 1.12 for specific ξ and for f = 1[x ∈ W 1 ]. In full generality, the convergence rate (1.23) is new.…”
Section: Remarksmentioning
confidence: 99%
“…We will refer to these generalizations as random combinatorial complexes (see [26] for a survey). It turns out that the Erdős -Rényi threshold for connectivity can be generalized to that of "homological connectivity," where the higher homology groups H k become trivial.In parallel to the study of combinatorial complexes, a line of research was established for random geometric complexes [3,5,24,42,43]. This type of complexes generalizes the model of the random geometric graph G(n, r) (introduced by Gilbert [18]), where vertices are placed at random in a metric-measure space, and edges are included based on proximity [38].…”
mentioning
confidence: 99%
“…Further justification for negative association as a measure of sparsity was seen in [37] where it was shown that the Palm measure of a negatively associated PP is 'stochastically weaker' than that of the original PP. In particular, the void probability increases for the Palm measure.…”
Section: Comparison Of Clustering To Poisson Point Processesmentioning
confidence: 99%
“…The motivation lies in the recent subject of topological data analysis. In an upcoming work [37], we study these models on more general stationary PPs using tools of stochastic ordering as well as asymptotic analysis of joint intensities and void probabilities. In particular, if we denote r con n ( ) as the critical contractibility radius for theCech complex on ∩ [−n 1/d /2, n 1/d /2] (i.e.…”
Section: First Passage Percolationmentioning
confidence: 99%